Implementasi Quadcopter Pembawa Arm Robot Pembersih Kaca Jendela Gedung Bertingkat - Haniffullah, Al; Bangsa, Insani Abdi; Stefanie, Arnisa (Edu Elektrika Journal, 2020)
The quadcopter is a multirotor drone that uses four drivester-controlled motors using flight controllers. The quadcopter is widely used in needs, such as inresearch, exploration, image retrieval, as well as observation. The study has been followed by a quadcopter implementation capable of steady flight and ofmaintaining altitude and position. The quadcopter's entire process of control and stability is controlled by a pid controller and is processed by the apm 2.8device as flight controller, which is equipped with a gyroscope sensor, an accelerometer and a GPS module. The results of implementation and research are:1. The quadcopter of 550mm x with a weight of 1.5 kg (5 lb) and uses 4 kilos on a brushless 980kv bike; 2. The quadcopter can maintain its altitude of altitudeusing a KP = 1.5 with a rise of time 0.5 seconds and a steady state average of 0.06 meters; 3. For a pitch and roll pitch system using KP value = 0.25, ki =0.15 and kd = 0.04Keywords— Quadcopter,Flight controller,Ardupilot Mega, PID System control.